Mice with myocyte deletion of vitamin D receptor have sarcopenia and impaired muscle function. Issue 6 (21st June 2019) - Girgis, Christian M.; Cha, Kuan Minn; So, Benjamin; Tsang, Michael; Chen, Jennifer; Houweling, Peter J.; Schindeler, Aaron; Stokes, Rebecca; Swarbrick, Michael M.; Evesson, Frances J.; Cooper, Sandra T.; Gunton, Jenny E.
Abstract: Background: It has long been recognized that vitamin D deficiency is associated with muscle weakness and falls. Vitamin D receptor (VDR) is present at very low levels in normal muscle. Whether vitamin D plays a direct role in muscle function is unknown and is a subject of hot debate. Myocyte‐specific deletion of VDR would provide a strategy to answer this question. Methods: Myocyte‐specific vitamin D receptor (mVDR) null mice were generated by crossing human skeletal actin‐Cre mice with floxed VDR mice. The effects of gene deletion on the muscle phenotype were studied in terms of body tissue composition, muscle tissue histology, and gene expression by real‐time PCR. Results: Unlike whole‐body VDR knockout mice, mVDR mice showed a normal body size. The mVDR showed a distinct muscle phenotype featuring reduced proportional lean mass (70% vs. 78% of lean mass), reduced voluntary wheel‐running distance (22% decrease, P = 0.009), reduced average running speed, and reduced grip strength (7–16% reduction depending on age at testing). With their decreased voluntary exercise, and decreased lean mass, mVDR have increased proportional fat mass at 20% compared with 13%. Surprisingly, their muscle fibres showed slightly increased diameter, as well as the presence of angular fibres and central nuclei suggesting ongoing remodelling. There were, however, no clear changes in fibre type and there was no increase in muscle fibrosis. VDR is a transcriptional regulator, and changes in the expression of candidate genes was examined in RNA extracted from skeletal muscle. Alterations were seen in myogenic gene expression, and there was decreased expression of cell cycle genes cyclin D1, D2, and D3 and cyclin‐dependent kinases Cdk‐2 and Cdk‐4 . Expression of calcium handling genes sarcoplasmic/endoplasmic reticulum calcium ATPases (SERCA) Serca2b and Serca3 was decreased and Calbindin mRNA was lower in mVDR muscle. Conclusions: This study demonstrates that vitamin D signalling is needed for myocyte function. Despite the low level of VDR protein normally found muscle, deleting myocyte VDR had important effects on muscle size and strength. Maintenance of normal vitamin D signalling is a useful strategy to prevent loss of muscle function and size.